ANALYSIS OF INDUSTRIAL-CAUSE OF MORBIDITY IN CONFECTIONERY FACTORY STAFF - I.U. IBRAGIMOV; A.B. BABAEV; Z.YA. YUSUPOV (Avicenna Tajik State Medical University, 2017)
Objective: Assessment of the dependence of morbidity with temporal disability (MTD) on the influence of unfavourable factors of the industrial environment of workers in a confectionery factory. Methods: The data from the sick lists for the analysis of the MTD were used over the period of three years from 345 workers in the main workshops of the "Shirin" confectionery factory. In the elaboration were taken the sick lists of workers who worked for at least 1 year in the caramel (115), confectionery-chocolate (120) and biscuit (110) shops. A total of 2,120 hospital sheets were analyzed. The average indices of the MTD, the Student's criteria, and the coefficients of the pair correlation were calculated. Results: The number of incapacity for work in the caramel, candy-chocolate and biscuit shops for three years was 123.8±12.8; 118.3±12.5 and 122.6±13.2 respectively. The number of days of incapacity for work in the first workshop is 1493.5±25.7, the second workshop - 1165.7±23.9, the third shop - 1384.2±25.1 days per 100 workers, while the duration of one case was 12.06±1.0; 9.85±1.1 and 11.29±1.0 days, respectively. The lowest indices were observed in candy-chocolate, the highest in the caramel workshop. According to the grading scale of E.L. Notkin (1979), the indicators in cases and days in all three shops correspond to a "high" level. There was statistically significant dynamic growth in MTD, depending on the age and length of service among workers in all shops. An analysis of the structure of morbidity showed that respiratory diseases (acute viral infections of upper respiratory tract, nasopharyngitis, tracheitis, bronchitis, pneumonia) occupy the largest proportion; second place - diseases of the cardiovascular system (hypertension, CHD). In the third place, the employees of the caramel and candy-chocolate shops had diseases of the digestive system, and in the workers of the biscuit shop - diseases of the musculoskeletal system. The relationship between MTD and unfavourable factors of the working environment are proved with the coefficients of the pair correlation. Conclusion: The indicators of MTD in confectionery production staff, in all three workshops, are estimated at a high level. These indicators depend on the degree of the activity of harmful production factors and standing, which dictates the need to develop recommendations, funds for improving working conditions and improving the health of workers in confectionery factories.